2011
DOI: 10.1177/0003319711419837
|View full text |Cite
|
Sign up to set email alerts
|

Increased Carotid Intima–Media Thickness is Associated With Higher SYNTAX Score

Abstract: The main purpose of this study was to investigate the relation between carotid intima-media thickness (CIMT) and coronary artery disease (CAD) complexity. Consecutive patients (n = 360) with CAD confirmed by coronary angiography were enrolled. Mean CIMT and the overall SYNTAX score (SXscore) were 0.87 ± 0.12 mm and 15 ± 9, respectively. In univariate analysis, there was a significant correlation between the overall SXscore and CIMT (r = .42, P < .001), age (r = .23, P < .001), hypertension (r = .27, P = 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…Similarly, Average CIMT value of zero-score female patients had significantly lower value than that of lowrisk SYNTAX score. In the study by Korkmaz et al, CIMT was found to be associated independently with the SYNTAX score (24). We found that patients with higher AGA stages had higher SYNTAX score and advanced stage of SYNTAX category both in males and females.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, Average CIMT value of zero-score female patients had significantly lower value than that of lowrisk SYNTAX score. In the study by Korkmaz et al, CIMT was found to be associated independently with the SYNTAX score (24). We found that patients with higher AGA stages had higher SYNTAX score and advanced stage of SYNTAX category both in males and females.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, this scoring system has been positively associated with PAD [ 9 , 10 ]. There is substantial evidence that carotid intima-media thickness (IMT) is, similarly to ABI, associated with SYNTAX score and may be considered as a marker of increased cardiovascular risk [ 11 , 12 ]. Moreover, IMT is a recommended measure of vascular age, which is usually different from the metric one, and thus may allow one to identify individuals with advanced subclinical atherosclerosis and as such to alternate cardiovascular risk estimates [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between carotid atherosclerosis and coronary artery disease (CAD) is well established [5] and some studies have demonstrated that the extent of carotid disease may predict the severity of CAD estimated by the SYNTAX score (SxScore) [6,7]. Conversely, in a recent paper investigating the relationship between SxScore and features of carotid atherosclerosis in patients with multivessel CAD, we found that the SxScore did not predict the presence of carotid disease [8].…”
Section: Introductionmentioning
confidence: 71%
“…A relation between CUS findings and CAD complexity evaluated by SxScore has been recently advocated [6,7]. The SxScore is an angiographic grading tool, endorsed by the European and US guidelines, which determines CAD complexity and facilitates clinicians in deciding the optimal revascularization strategy [18].…”
Section: Discussionmentioning
confidence: 99%